Mewujudkan Milenial Bijak Sadar Pajak Di Masa Pandemi Covid-19 - Ferry Irawan; Bintang Septian Simbolon; Caesario Santo H. Gultom; Dhea Monica Rudi; Ebsan Tangguh Septino; Esti Marintan Sianturi; Grace Shelpia Maduma Manik; Karina Deriska; Muhammad Hammam Rafati Lubis; Perdana Ratus Mangiring Sinaga; Tania Naftali Sianturi (PT WIM Solusi Prima, 2021)
The young generation, including millennials, is an important component in national development. Millennials can occupy important positions in the future. Therefore, the level of knowledge and awareness of taxes is a strategic and important thing to understand. Community Service Activities through this web seminar (webinar) aim to provide millennials with tax literacy. The materials presented in the webinar include basic tax concepts, types of taxes, misconceptions about taxes, and the importance of being aware of taxes for the millennial generation. There are several steps involved in the implementation of this webinar. First, the presentation from the resource person. Second, it was followed by a good discussion through the chat box. Third, game activities. At the end of the event there are prizes for active participants. Based on feedback from webinar participants, this activity increases the knowledge and understanding of the participants regarding taxes.